El ensayo desde su (inter) conexiones teóricas - Vargas Durán, Ricardo Ignacio (2016)
With this article we approach studies dedicated to the literary gender, best known as Essay, issue of knowledge where it is implied to enter in a wide institutional-academic debate, that is full of intern links, still valid in the area where many problems are inferred, that form part of the multiple theories for the study of the essay. That’s the reason why this article analyses the probable links in the mentioned literary practice. From the different conceptualizations that recognize the procedures in an essay theory. In this perspective the location of the “theoric reader” is established. This is important to understand so that the variables inferred from the spectrum speech-theory are comprehended and also to propose the systematic studies from the essay in the literary region of Central America.